Adopting Virtual Visits for Parkinson's Disease Patients During the COVID-19 Pandemic in a Developing Country - Shalash, Ali; Fathy, Mai; Dawood, Noha L.; Hamid, Eman (Frontiers in Neurology, 2020)
Objective: Telemedicine has been increasingly used, especially during the COVID-19 pandemic; however, limited data are available from developing countries. The present study aimed to evaluate the feasibility, satisfaction of patients and physicians and the quality of service provided during virtual visits for Parkinson’s disease (PD) patients during the COVID-19 pandemic and the associated limitations. Methods: Thirty-nine PD patients were contacted to schedule virtual visits using the Zoom application. Thereafter, we rated the feasibility, satisfaction and the quality of service provided by virtual visits using patients’ and physicians’ questionnaires. Results: Twenty-one out of 39 PD patients were scheduled for virtual visits. Nineteen virtual visits out of 21 (90.5%) were conducted successfully; 16 of these were accomplished in the first attempt (76.2%). The scores of satisfaction, quality of service, and set-up/preparation were 9.5 (8.5–10), 9.5 (9–10), and 8 (5–10) for the patients and 9 (7–10), 8 (6–10), and 10 (10–10) for the physicians, respectively. The average time that was saved was 270.79 ± 142.17 minutes, while an average of 76.38 ± 95.15 km of travel was avoided for the patients per visit. The most common limitations for conducting virtual visits were a lack of internet connection and the inability to use technology (75%). Conclusions: The present study showed the feasibility and high satisfaction level of patients and physicians as well as favorable service quality of virtual visits for PD in a developing country during the COVID-19 pandemic. However, the lack of internet connectivity and inability to use technology were the main limitations.